(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2017)
The research paper is on the analysis of the financial performance of the AOS system with the help of ratio analysis. The practice of ratio analysis has been used by financial market participants and managers of firms for almost a century. Ratio analysis become very essential for all the organisation to survive in the market for a longer period. The research is expected to help understanding the overall financial performance of the AOS systems. We have analyzed the account ting information of the company through ratios and construed in such a way that can be easily understood by all.